2015
DOI: 10.1155/2015/847320
|View full text |Cite
|
Sign up to set email alerts
|

Topical Anti-Inflammatory Effects of Isorhamnetin Glycosides Isolated fromOpuntia ficus-indica

Abstract: Opuntia ficus-indica (OFI) has been widely used in Mexico as a food and for the treatment of different health disorders such as inflammation and skin aging. Its biological properties have been attributed to different phytochemicals such as the isorhamnetin glycosides which are the most abundant flavonoids. Moreover, these compounds are considered a chemotaxonomic characteristic of OFI species. The aim of this study was to evaluate the effect of OFI extract and its isorhamnetin glycosides on different inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(39 citation statements)
references
References 58 publications
(62 reference statements)
0
38
0
Order By: Relevance
“…In this study, the authors showed for the first time that HEVP and EAEVP have topical anti-inflammatory effect, which is possibly related to the presence of secondary compounds, since some flavonoids (rutin, luteolin, and apigenin) were identified in EAEVP and this effect may involve different mechanisms in the cutaneous inflammation [28,29]. Rutin, for example, inhibited the xilol-induced ear edema and reduced the cell migration and the levels of cytokines were also observed [30], while luteolin exhibits anti-inflammatory effects by blocking the activity of heat shock protein 90 in macrophages [31].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors showed for the first time that HEVP and EAEVP have topical anti-inflammatory effect, which is possibly related to the presence of secondary compounds, since some flavonoids (rutin, luteolin, and apigenin) were identified in EAEVP and this effect may involve different mechanisms in the cutaneous inflammation [28,29]. Rutin, for example, inhibited the xilol-induced ear edema and reduced the cell migration and the levels of cytokines were also observed [30], while luteolin exhibits anti-inflammatory effects by blocking the activity of heat shock protein 90 in macrophages [31].…”
Section: Discussionmentioning
confidence: 99%
“…14 This fruit also represents an interesting source of functional and healthy compounds, including total phenols, flavonoids, carotenoids, betalains, vitamins, free amino acids and the minerals Ca, Na, Mg, Zn, Fe, Mn and Se, 5,[15][16][17] with varying biological activities. 18,19 The identification of geographic provenience of food represents, first, a current and global issue for consumers, who show increasing interest in the traceability of food supply, and, second, an important quality parameter to bring about the protected denomination of origin for some foods. 20 Several techniques are applied to the study of food quality and traceability, such as foodomic methods, chromatographic and spectroscopic techniques, among others, [21][22][23][24][25] but multi-elemental analysis (MEA) is the most commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal use of V. polyanthes for cicatrisation and cutaneous damage was the crucial stimulus for this research. For the first time, EEVPB and EFVPB showed topical anti-inflammatory effect, which can be related to the presence of secondary metabolites, since several compounds (3,7-dimethoxy-5,3',4'-trihydroxyflavone, piptocarphin A, 3',4'-dimethoxyluteolin, glaucolide A, 3,5-di-O-(E)-caffeoylquinic acid, 4,5-di-O-(E)-caffeoylquinic acid, luteolin, quercetin, protocatechuic acid, quercetin-3-O-β-glucoside, apigenin and isorhamnetin) have been identified in this plant 8,12 and this effect may involve different mechanisms in the cutaneous inflammation 29 .…”
Section: Mg/ear Positive Control Group) and Acetone (Vehicle Negatimentioning
confidence: 97%